(untitled) (Medico Legal Update, 2021)
Background: Endurance sports greatly affect fluid requirements. The exercise that is too heavy will cause a lot of body fluids to come out. Providing sports drinks with carbohydrate and electrolyte content has more benefits for athletes. One of them is an isotonic drink formula with the addition of gum Arabic. The food safety factor in isotonic drink formulas is very important to prevent side effects due to the contamination of food or beverages that can endanger health. Objectives to determine the food safety of the isotonic drink formula with the addition of gum Arabic. Method: This study is the pre-experimental. Food safety, which includes microbial and metal contaminants, was analyzed at the Makassar Health Laboratory Center. The results showed that the isotonic beverage formula with the addition of gum Arabic was safe from metal contamination. Results of the microbial contamination test shows that Biunik (F1) is an isotonic drink formula with the addition of safe Arabic gum, while other formulas still exceed the quality requirements of isotonic drinks in Indonesia based on ISN 01-4452-1998.